2018
DOI: 10.3390/catal8050197
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Environmental Application of Bio-Based Materials as Auxiliaries in Photocatalytic Processes

Abstract: Sustainable alternative substrates for advanced applications represent an increasing field of research that attracts the attention of worldwide experts (in accordance with green chemistry principles). In this context, bio-based substances (BBS) isolated from urban composted biowaste were purified and characterized. Additionally, these materials were tested as auxiliaries in advanced oxidizing photocatalytic processes for the abatement of organic contaminants in aqueous medium. Results highlighted the capabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
(82 reference statements)
0
18
0
Order By: Relevance
“…37%) and the spin-label 5-doxylstearic acid, free radical (5-DXS, CAS 29545-48-0) were purchased from Sigma Aldrich. The bio-based substances (BBS-GC) were isolated from composted urban biowastes, following a procedure reported in the literature [61].…”
Section: Methodsmentioning
confidence: 99%
“…37%) and the spin-label 5-doxylstearic acid, free radical (5-DXS, CAS 29545-48-0) were purchased from Sigma Aldrich. The bio-based substances (BBS-GC) were isolated from composted urban biowastes, following a procedure reported in the literature [61].…”
Section: Methodsmentioning
confidence: 99%
“…Materials such as compost, anaerobic digestate, and organic residues from mechanical-biological treatment of UBW can be studied as biomass that could be used to feed a biorefinery [ 21 ]. It was previously demonstrated that with this approach, it is possible to extract from UBW, anaerobically and/or aerobically treated, bio-based substances (hereinafter BBS) featuring similarly to soil humic substances under the structural and physicochemical point of view [ 22 , 23 ]. Bio-based substances have been tested in several technological and environmental applications, including wastewater treatment [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compost-derived bio-based substances (BBS-Cs) have been previously obtained from commercially composted urban biowastes [ 38 ] following a standard procedure for the humic acid isolation from soils; these composted biowastes are derived from urban public park trimmings and home gardening residues aged for more than 180 days [ 22 ]. After isolation, BBS-Cs have been characterized for their physico-chemical features [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is the standard definition, since several further (and more complex) chemical structures showing amphiphilic properties are possible (e. g., humic substances, (co)polymers, crown ethers, and so on). [53][54][55][56] According to the hydrophilic functional groups, they can be classified as ionic (charged) or non-ionic (polar uncharged) surfactants. Due to their peculiar structure, they can self-organize themselves into supramolecular aggregates (micelles), able in preventing the aggregation phenomena but also exploitable in soft-templating processes.…”
Section: Growth Mechanism and Role Of Surface-regulating Agentsmentioning
confidence: 99%